Automation of the Peak Fitting Method in Bone FTIR Microspectroscopy Spectrum Analysis: Human and Mice Bone Study - Gardegaront, Marc; Farlay, Delphine; Peyruchaud, Olivier; Follet, Hélène (Journal of Spectroscopy, 2018)
FTIR microspectroscopy (FTIRM) is a commonly used nondestructive method to characterise thin bone sections. However, spectrum analysis methods are often highly sensitive to small variations (e.g., boundary limits), thus implying a time-consuming and redundant analysis process. To solve this issue, software has been developed based on several algorithms to automate the analysis. Furthermore, a rigorous framework has been established concerning the peak fitting method to obtain the systematic best potential solution. Validation of the automatic method has been performed by comparison with the manual method. Results and validation proved the reliability of the automatic process. The developed algorithms provide the means necessary to fully compare the results between bone FTIRM studies and between different laboratories.